2018
DOI: 10.1002/mrd.22989
|View full text |Cite
|
Sign up to set email alerts
|

Identification and comparative analysis of the ovary and testis microRNAome of mud crab Scylla paramamosain

Abstract: The role of microRNA (miRNA) in reproductive regulation is attracting increasingly more attention. In this study, we obtained 9,643,114 and 15,498,999 raw reads from the ovary and testis library of important farmed mud crab Scylla paramamosain, respectively. After data mining, a total of 4,096,464 and 11,737,973 mappable small RNA sequences remained for analysis. By mapping to the reference genome and expressed sequence tag (EST) of Daphnia pulex and other crabs, a total of 1,417 miRNAs were identified. On the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…Liu, Wu, and Hua () proved that miR‐34c performed some particular functions during the development of mammalian germ cells. Moreover, our miRNA transcriptome data and qRT‐PCR results confirmed that miR‐34 was differentially expressed between ovary and testis (Jia et al, ). In this study, the target genes of miR‐34 that are related to the gonadal development were predicted and validated in eyestalk.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Liu, Wu, and Hua () proved that miR‐34c performed some particular functions during the development of mammalian germ cells. Moreover, our miRNA transcriptome data and qRT‐PCR results confirmed that miR‐34 was differentially expressed between ovary and testis (Jia et al, ). In this study, the target genes of miR‐34 that are related to the gonadal development were predicted and validated in eyestalk.…”
Section: Discussionsupporting
confidence: 71%
“…Even in invertebrates, miRNAs are required for oocyte maturation and ovulation because worms are sterile and fail to ovulate with reduced miRNA biogenesis due to loss of Drosha or Pasha/DGCR8 activity (Kadener et al, ). MiR‐9, miR‐9c, miR‐263a, and miR263b may have effects on many genes in mud crab, especially the genes related to gonadal development (Jia et al, ). All of these research works suggest that miRNAs are involved in the regulation of reproduction, especially in gonadal development.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, some miRNAs, including miR-34c-5p, miR-153-5p, and miR-749, were expressed exclusively in Nile tilapia XX gonads at five days post-hatching, whereas miR-1306-5p, miR-132b, and miR-18c were expressed exclusively in the XY gonads [ 21 ]. MiRNA expression patterns have also been studied in the gonads of Oplegnathus punctatus [ 22 ], Scylla paramamosain [ 23 , 24 ], Acipenser schrenckii [ 25 ], Trachinotus ovatus [ 26 ], and Odontobutis potamophila [ 27 ]. These studies help to clarify the roles of miRNAs in sexual differentiation and gonadal development.…”
Section: Introductionmentioning
confidence: 99%
“…With the developments of high-throughput sequencing technologies, a large number of miRNA transcriptome profiles have been obtained and characterized in various crustaceans, such as P. trituberculatus [21, 22, 27], E. sinensis [20, 23, 25], and S. paramamosain [24, 26, 28, 29]. Furthermore, miRNAs have been demonstrated to be vital for regulating gene expression and several biological functions, such as growth regulation [21], metabolism processes [22], and responses to viral infection [24].…”
Section: Discussionmentioning
confidence: 99%